Evaluating Customer Satisfaction Through Customer Value: The Role Of Food Quality, Service Quality, And Physical Environment: Case Study In Mie Gacoan Indonesia Restaurant In South Tangerang City - Windarko, Windarko; Silaban, Wiltasar Daniel Christover; Maharani, Putri; Yusup, Tiara Yuristina (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This study investigates the relationship between customer satisfaction and customer value, focusing on the significance of food quality, service, and physical environment in Mie Gacoan Indonesia Restaurant located in South Tangerang City. By employing a case study approach, data was collected from customers to assess their perceptions and satisfaction levels regarding the mentioned factors. Statistical analysis techniques were applied to analyze the data and determine the impact of food quality, service, and physical environment on customer satisfaction. The findings reveal important insights into the dynamics of customer satisfaction in the restaurant industry and emphasize the critical role of customer value in enhancing overall satisfaction. This study contributes to the existing literature by providing empirical evidence and practical implications for restaurant management aiming to improve customer satisfaction and loyalty.